Cyto/chemokine profile of in vitro scratched keratinocyte model: Implications of significant upregulation of CCL20, CXCL8 and IL36G in Koebner phenomenon. Issue 1 (April 2019) - Furue, Kazuhisa; Ito, Takamichi; Tanaka, Yuka; Yumine, Ayako; Hashimoto-Hachiya, Akiko; Takemura, Masaki; Murata, Maho; Yamamura, Kazuhiko; Tsuji, Gaku; Furue, Masutaka
Highlights: Pathomechanism of scratch-induced Koebner phenomenon in psoriasis is unknown. Scracth injury on confluent keratinocytes upregulates CCL20, CXCL8, IL36G and TNF . Protein secretion is observed only in CCL20 and CXCL8. CCL20 and CXCL8 secretion is partially inhibited by steroid. Benzopyrene synergistically enhance scratch-induced CCL20 but not CXCL8 secretion. Abstract: Background: Scratch injury induces Koebner phenomenon in psoriasis. Smoking is also a risk factor for psoriasis. Keratinocytes can produce various psoriasis-related molecules including TNF, IL1 A, IL1B, IL6, IL12B, IL17C, IL23 A, IL36 A, IL36B, IL36 G, CXCL1, CXCL2, CXCL8, CXCL9, CXCL10, CCL20, IFNB, and CAMP. However, the scratch-induced molecular profiling remains elusive. Objective: To profile the induction pattern of above-mentioned psoriasis-related and keratinocyte-derived molecules by scratch injury in the presence or absence of anti-psoriatic drugs or benzo[a]pyrene, a major environmental pollutant of tobacco smoke. Methods: Confluent normal human keratinocytes were scratched and molecules were assayed by qRT-PCR, ELISA and Western blotting with or without drugs and benzo[a]pyrene. Results: Among the 18 molecules, the scratch injury on a confluent keratinocyte sheet significantly and selectively upregulated the mRNA expression of four cyto/chemokines, CXCL8, CCL20, IL36G, and TNF, in a scratch-line-number-dependent manner under either low- or high-calcium condition. However, significant protein secretion was only demonstrated for CXCL8 and CCL20. The IL36 G protein was not secreted, but its intracellular level was significantly upregulated by scratch injury, whereas neither the secretion nor the intracellular level of TNF protein was affected by scratch injury. Dexamethasone, but not maxacalcitol nor the phosphodiesterase 4 inhibitor apremilast, partially inhibited the CXCL8 and CCL20 secretion. Benzo[a]pyrene significantly and synergistically enhanced the scratch-induced CCL20 secretion that may explain why smoking is a risk factor for psoriasis. Conclusion: CCL20 and to a less extent CXCL8 may play a key role in triggering the Koebner phenomenon after scratch injury to keratinocytes.